IN SILICO INVESTIGATION OF POTENTIAL BIOLOGICAL TARGETS OF TRIAZINE-BASED SULFONAMIDES RELATED TO NEPHROTOXICITY (CIPEEX, 2025)
Sulfonamides are antibiotics that inhibit folic acid production in bacteria, thereby preventing their growth. They are commonly used in the treatment of infections and may be repurposed for other applications, such as herbicides. The inhibition of acetolactate synthase, an essential enzyme for the biosynthesis of amino acids in plants, represents an important target for weed control. This study aimed to investigate potential biological targets related to the nephrotoxicity of sulfonamide-based herbicides through in silico approaches. The methodology involved bioactivity screening of the compounds using the PharmMapper and ProTox 3.0 servers. The results suggested possible renal risks and identified seven biological targets that may potentially interact with the sulfonamides investigated in this study: Cathepsin B, Phospholipase A2, Carbonic Anhydrase 2, Aliphatic Amidase, Androgen Receptor, GDP-mannose 6-dehydrogenase, and Prothrombin. The identification of these biological targets may contribute to understanding how such sulfonamides interact in the human body, supporting the development of more selective, safer, and sustainable pesticides.
Keywords: Acetolactate synthase; toxicity; herbicides